The epistemology of development, evolution, and genetics : selected essays - Burian, Richard M. (Cambridge studies in philosophy and biology., 2005)
These essays examine the developments in three fundamental biological disciplines - embryology, evolutionary biology, and genetics. These disciplines were in conflict for much of the twentieth century and the essays in this collection examine key methodological problems within these disciplines and the difficulties faced in overcoming the conflicts between them.